A Novel Antithrombotic Protease from Marine Worm Sipunculus Nudus - Ge, Ya-Hui (Int J Mol Sci, 2018)
Sipunculus nudus, an old marine species, has great potential for use as functional seafood due to its various bioactivities. Its potential antithrombotic activity pushed us to isolate the bio-active components bio-guided by tracking fibrinolytic activity. As a result, a novel protease named as SK (the kinase obtained from S. nudus) was obtained, which possessed a molecular weight of 28,003.67 Da and 15 N-terminal amino acid sequences of PFPVPDPFVWDTSFQ. SK exerted inhibitory effects on thrombus formation through improving the coagulation system with dose-effect relationship within a certain range. Furthermore, in most cases SK got obviously better effect than that of urokinase. With the help of untargeted mass spectrometry-based metabolomics profiling, arachidonic acid, sphingolipid, and nicotinate and nicotinamide mechanism pathways were found to be important pathways. They revealed that the effect mechanism of SK on common carotid arterial thrombosis induced by FeCl(3) was achieved by inhibiting vessel contraction, platelet aggregation, adhesion, and release, correcting endothelial cell dysfunction and retarding process of thrombus formation. This study demonstrated SK was a promising thrombolytic agent on the basis of its comprehensive activities on thrombosis, and it should get further exploitation and utilization.